2022
DOI: 10.1111/glob.12368
|View full text |Cite
|
Sign up to set email alerts
|

Bangladeshi women migrants amidst the COVID‐19 pandemic: Revisiting globalization, dependency and gendered precarity in South–South labour migration

Abstract: The COVID‐19 pandemic has triggered unprecedented societal disruption and disproportionately affected global mobility dynamics. Within such a troubled and intensifying crisis, the intersection of migration and gender is even more unsettling. Since the pandemic outbreak, Bangladesh witnessed a colossal crisis among millions of Bangladeshi migrants working overseas—a considerable section of them are women. By highlighting the plight of the Bangladeshi women migrants in the Gulf Cooperation Council (GCC) countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…While many workers with regular job contracts and stable incomes have been exposed to a situation of “absolute unpreparedness” ( Lo and Hsieh, 2020 ), protection needs demand a gender analysis. However, “an isolated view on gender obscures the relationality and internal differentiation of social categories which operate alongside intersectional hierarchies” ( Bilecen et al, 2019 : 2), since it operates with other markers of difference, such as ethnicity, age, marital and education status, and social class ( Ansar, 2022 ). As such, gender needs to be understood within “the set of mutually constitutive structures and practices which produce gender differentiation, gender inequalities, and gender hierarchy in a given society” ( Orloff, 1996 : 52).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…While many workers with regular job contracts and stable incomes have been exposed to a situation of “absolute unpreparedness” ( Lo and Hsieh, 2020 ), protection needs demand a gender analysis. However, “an isolated view on gender obscures the relationality and internal differentiation of social categories which operate alongside intersectional hierarchies” ( Bilecen et al, 2019 : 2), since it operates with other markers of difference, such as ethnicity, age, marital and education status, and social class ( Ansar, 2022 ). As such, gender needs to be understood within “the set of mutually constitutive structures and practices which produce gender differentiation, gender inequalities, and gender hierarchy in a given society” ( Orloff, 1996 : 52).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Amid various state-led support programs, migrants received little attention during the peak of the pandemic in their countries of origin and destination ( Gentilini, 2021 ). This is demonstrated through migrants’ forced deportation, arbitrary dismissal, and exclusion from social service schemes launched by many receiving states in the aftermath of the pandemic ( Ansar, 2022 ; Menon and Vadakepat, 2021 ). Moreover, the remittance sent by the migrant workers is a ‘crucial lifeline’ for at least 800 million relatives living back home in low- and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors conclude that the episode revealed challenges for the Canadian government to support international students in the future. Ansar (2023) offers a different perspective on the effects of the Covid-19 pandemic on a contrasting group of international migrants, Bangladeshi women migrants living and working in the Gulf Cooperation Council (GCC) countries. The research offers new theorical insights into the junctures between globalization 'from below' , migration and gendered labour.…”
mentioning
confidence: 99%
“…The accepted papers offer both significant individual contributions, but also as a collective, a deep understanding of how the challenge of Covid‐19 reconfigures contemporary globalization, international migration, transnationalism, supply‐chains, and ensuing global networks across society. Broadly speaking, the papers covered several inter‐related theoretically and evidence‐based topics from international migration, mobilities, and proximity (Ansar, 2023 ; Hari et al., 2023 ) to transnational immobilities (Kempny, 2023 ; Simola et al., 2023 ; Skovgaard‐Smith, 2023 ) to diasporic and transnational communities (Ceccagno & Thurø, 2023 ; Müller, 2023 ; Yamamura, 2023 ) and forced labour in global value chains (Hughes et al., 2023 ). Collectively, the authors should be highly commended for their resilience and inventiveness in completing original empirical work during a period of unprecedented disruption for themselves, their subjects and their institutions.…”
mentioning
confidence: 99%